Young children's argumentative contributions - Perret-Clermont, Anne-Nelly; Greco, Sara (Oxon, New-York: Routledge, 2023)
Drawing on a rich tradition of dialogue-centered studies of children’s talk in conversation with peers and adults, the authors focus on young children’s contributions to argumentative discussions. The most promising research areas in this field are grouped around three keywords: the dialogue, the implicit content within argumentative inference, and the context of the discussion. For each of these areas, the authors discuss existing research, proposing empirical examples of children’s talk and examining how the analysis of these examples not only advances the understanding of children’s argumentation but also sheds new light on the models relative to adults’ argumentation. The findings of this chapter illustrate that children’s contributions should not be considered as isolated productions. They are better understood if placed within the dialogic setting in which they are produced, taking into account adults’ roles and expectations, children’s interpretations of such settings, and, more in general, the design of the dialogue space. Moreover, the analysis of inference shows that often children’s contributions do not differ from adults’ in terms of the argument schemes used, but in terms of material-contextual premises (endoxa). These findings invite further discourse and argumentation research on adults’ expectations and children’s interpretations of dialogic settings, including educational contexts.